If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 20 = x + 2 Reorder the terms: 20 + 3x = x + 2 Reorder the terms: 20 + 3x = 2 + x Solving 20 + 3x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 20 + 3x + -1x = 2 + x + -1x Combine like terms: 3x + -1x = 2x 20 + 2x = 2 + x + -1x Combine like terms: x + -1x = 0 20 + 2x = 2 + 0 20 + 2x = 2 Add '-20' to each side of the equation. 20 + -20 + 2x = 2 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = 2 + -20 2x = 2 + -20 Combine like terms: 2 + -20 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 5x-1/6x-9-5x-10/8x^2-18=9x-4/8x-12 | | 3x+6+9=12 | | -3(4T-1)=-(t-14) | | 9h-27=36 | | 4/5x5/16 | | -5b+7-4b-2-b=-15 | | 4(3+4)-3=25 | | 2x+20=94 | | 5a+9b=360 | | 4/3T=-36 | | 4(3+4x)=25 | | 4c-8=5c+15 | | (x-7)(x+3)=24 | | 10p-7=24 | | -11.4-m=10.9 | | 20p-7=24 | | 37+(9x-1)=90 | | 3x/4-2/3=5/6 | | (3y+7)(-4x+2)= | | (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 | | 56+(7x-1)=90 | | (15/8)=((17-x)/x) | | 5n(4n+1)=0 | | 16+5a=31 | | 10x-6/3-5x |